Legal Review of Land Certificates Affected by Forest Areas in Indonesia - Marisyah Taher; Gunawan Djajaputra (Dinasti Research, 2024)
This research examines the legal review of land certificates affected by forest areas according to the Indonesian Basic Agrarian Law (UUPA) and its implications within forest regions. Under the UUPA, land encompasses not only the surface but also the subsoil, establishing legal relationships between individuals or legal entities and the land, which results in specific legal statuses. The UUPA regulates land rights, including permanent rights, statutory rights, and temporary rights. Land registration is mandated to ensure legal certainty for rights holders and to provide protection by issuing valid certificates. These certificates serve as strong evidence of ownership, though they can be annulled if administrative or material errors are found. In the context of forest areas, land regulation becomes more complex. Forest areas, as stipulated by the Forestry Law, require protection and must be exempt from individual or corporate rights, as such rights can threaten the sustainability of forest ecosystems. To address land ownership conflicts within forest regions, the government has issued Presidential Regulations that govern the processes for managing, organizing, and resolving disputes in forest areas through various mechanisms, including social forestry programs. Agrarian reform is also implemented through land redistribution to promote welfare and equity. However, despite regulations governing certificates within forest areas, no specific policy exists regarding the annulment of certificates in these zones. Annulment is needed as a legal remedy for ownership disputes that may arise due to administrative defects or illegality